Nickel substituted effect of on structural, Mössbauer and dielectric properties of spinel-type lithium ferrites - Mazurenko, Ju. (Physics and Chemistry of Solid State, 2020)
Ni-substituted lithium ferrite Li0.5-x/2NixFe2.5-x/2O4, where (х=0.0, 0.2, 0.4, 0.6, 0.8, 1.0) synthesized through sol-gel auto-combustion method was investigated for its structural, Mossbauer, and dielectric properties. At low doses of substitution, two spinels of the same composition coexist in the structure, one of spatial group P4332, so-called spinel with superstructure, in which the iron and lithium ions are arranged along the crystallographic direction <110> and the other is a spatial group Fd3m, random spinel. The presence of both spinels is observed at low content of the doped element (x = 0.2 and 0.4). In case of increase Ni2+ ions, random component disappears and only the ordered phase remains. The particle sizes of the synthesized product are around 22-45 nm. According to the proposed cationic distribution of Nickel ions are localized in the A-site and lithium ions in the B-site. Iron ions are redistributed over both sites at a ratio of about 1:2. It is shown, that the conductive and dielectric properties of the synthesized powders have a frequency dependence characteristic of ferrite materials, the behavior of which is explained based on the hopping mechanism of conductivity and inter-grain polarization.